Nobiletin Inhibits Inflammatory Reaction in Interleukin-1β-Stimulated Human Periodontal Ligament Cells - Yoshitaka Hosokawa; Ikuko Hosokawa; Kazumi Ozaki; Takashi Matsuo (MDPI AG, 2021)
The immune response in periodontal lesions is involved in the progression of periodontal disease. Therefore, it is important to find a bioactive substance that has anti-inflammatory effects in periodontal lesions. This study aimed to examine if nobiletin, which is found in the peel of citrus fruits, could inhibit inflammatory responses in interleukin (IL)-1β-stimulated human periodontal ligament cells (HPDLCs). The release of cytokines (IL-6, IL-8, CXCL10, CCL20, and CCL2) and matrix metalloproteinases (MMP-1 and MMP-3) was assessed by ELISA. The expression of cell adhesion molecules (ICAM-1and VCAM-1) and the activation of signal transduction pathways (nuclear factor (NF)-κB, mitogen-activated protein kinases (MAPKs) and protein kinase B (Akt)) in HPDLCs were detected by Western blot analysis. Our experiments revealed that nobiletin decreased the expression of inflammatory cytokines, cell adhesion molecules, and MMPs in IL-1β-stimulated HPDLCs. Moreover, we revealed that nobiletin treatment could suppress the activation of the NF-κB, MAPKs, and Akt pathways. These findings indicate that nobiletin could inhibit inflammatory reactions in IL-1β-stimulated HPDLCs by inhibiting multiple signal transduction pathways, including NF-κB, MAPKs, and Akt.